Relationship Between Effort-Reward Imbalance, Over-Commitment and Occupational Burnout in the General Population: A Prospective Cohort Study - Yara Shoman; Setareh Ranjbar; Marie-Pierre Strippoli; Roland von Känel; Martin Preisig; Irina Guseva Canu (Frontiers Media S.A., 2023)
Objectives: To prospectively investigate the association between Effort-Reward Imbalance (ERI) and over-commitment and the scores of the burnout dimensions over a 4 years follow-up period considering potential confounders.Methods: Data stemmed from CoLaus|PsyCoLaus, a population-based cohort study including 575 participants (mean age 55 years, 50% men). Participants completed the Maslach Burnout Inventory-General Survey, ERI and over-commitment questionnaires at baseline (T1) and after a 4 years follow-up (T2), and provided demographic, behavioral, psychiatric, personality and social support information through self-reported questionnaires and semi-structured interviews. Serially adjusted linear regression models were used.Results: ERI and over-commitment were not associated longitudinally with any of the burnout dimensions when controlling for confounders. One standard deviation increases in the scores of exhaustion, cynicism and professional efficacy were associated with one standard deviation increase in the scores of the same burnout dimensions longitudinally, and these associations were independent of the effects of ERI and over-commitment.Conclusion: Future studies should re-examine the effect of ERI and over-commitment on workers' burnout, considering the effects of confounders.